Impact of smart health systems on the behavior of older adults under community healthcare - Jing Zhao; Liangyu Wang; Kaimeng Guo (Frontiers Media S.A., 2022)
BackgroundWith the trend of world population aging, a good community health care system will determine whether the elderly can get good medical conditions. How to improve the community health care system can study how the behavior of the elderly affects it.ObjectiveThis paper is based on the analysis of the current situation of population aging at home and abroad.MethodsOn the premise of analyzing the demand and behavior of elderly people seeking medical treatment and the function of community health service institutions. Literature research was conducted to analyze the influencing factors of community health care needs and elderly people's medical seeking behavior at home and abroad. Then the elderly in Tianjin were investigated by issuing questionnaires, and the law of medical treatment behavior of the elderly in Tianjin was calculated. Combined with the results of relevant investigations abroad, the common phenomenon is summarized. Finally, the analysis method of intelligent medical system is proposed, and the design process of system acquisition module and user usage mode are given.ResultThe smart medical system can bring great convenience to the elderly and community healthcare.DiscussionIt emphasizes the powerful functions of smart health systems and their future importance for the health care of the elderly.